Legal Implications of Electronic Banking in Nigeria - Orifowomo, Odunola Akinwale (2015)
This study critically, examined the various components of electronic banking (e-banking) and their impact on the industry. It analysed the legal issues generated by electronic banking in Nigeria, the existing legal and institutional frameworks for the banking industry, and highlighted their inadequacy in meeting the challenges of electronic banking. It also developed an appropriate legal framework for e-banking in Nigeria